Changes in Carbohydrate Composition in Fermented Total Mixed Ration and Its Effects on in vitro Methane Production and Microbiome - Li, Yang; Lv, Jingyi; Wang, Jihong; Zhou, Shuang; Zhang, Guangning; Wei, Bingdong; Sun, Yukun; Lan, Yaxue; Dou, Xiujing; Zhang, Yonggen (Frontiers in Microbiology, 2021)
The purpose of this experiment was to investigate the changes of carbohydrate composition in fermented total mixed diet and its effects on rumen fermentation, methane production and rumen microbial community in vitro. The concentrate-to-forage ratio of the total mixed ration (TMR) was 4:6, and TMR was ensiled with lactic acid bacteria and fibrolytic enzymes. The results showed that different TMRs had different carbohydrate compositions and subfractions, fermentation characteristics, and bacterial community diversity. After fermentation, the FTMR group had lower contents of neutral detergent fiber, acid detergent fiber, starch, nonfibrous carbohydrates, and carbohydrates. Moreover, the fraction of carbohydrates that was considered undegradable in the FTMR group was significantly lower than that in the TMR group. In addition, lactic acid content and relative abundance of Lactobacillus in FTMR group was higher. Compared with the TMR group, the in vitro ammonia nitrogen and total volatile fatty acid concentrations as well as the molar proportion of propionate were increased in the FTMR group. However, the ruminal pH, molar proportion of acetate and butyrate, and methane production were significantly decreased in the FTMR group. Notably, we found that the relative abundance of ruminal bacteria was higher in FTMR than in TMR samples, including Prevotella, Coprococcus, and Oscillospira. At the same time, we found that the diversity of methanogens in the FTMR group was lower than that in the TMR group. The relative abundance of Methanobrevibacter significantly decreased, while the relative abundances of Methanoplanus and vadinCA11 increased. The relative abundances of Entodinium and Pichia significantly decreased in the FTMR group compared with the TMR group. These results suggest that FTMR can be used as an environmentally cleaner technology in animal farming due to its ability to improve ruminal fermentation, modulate rumen microbiota, and reduce methane emissions.